Analisis Kualitas Pelayanan Perpustakaan Daerah di Kota Depok - Erlina Nur Azizah; Nida Handayani (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The reading interest index in Indonesia according to the UNESCO survey is still relatively low, so support from various parties is needed, one of which is quality library facilities and infrastructure. Therefore, it is necessary to analyze the quality of library services. This study aims to assess the quality of regional library services in Depok City using a qualitative descriptive approach. The focus of this study refers to the five dimensions of Prasuraman's theory, namely Responsiveness, Assurance, Tangible, Empathy, and Reliability.Data collection was carried out through observation, interviews, and documentation. The results of the study showed that the library succeeded in providing accurate, timely, and consistent services in accordance with strict SOPs and routine evaluations, reflecting a high level of reliability. In terms of responsiveness, the library is responsive to visitor needs through mobile library services, digital services, and efficient complaint management. Service quality is guaranteed through regular training for staff and friendly attitudes of officers, creating a comfortable and trusted environment. Empathy is shown through an approach that is tailored to visitor needs, providing personal attention that makes visitors feel appreciated. Despite limitations in facilities, the library strives to provide adequate services, including facilities for people with disabilities, especially the blind and deaf.